การนำเสนอกลยุทธ์การบริหารงานวิชาการตามระบบการประกันคุณภาพการศึกษาในโรงเรียนประถมศึกษาขนาดเล็กแบบรวมเรียน - อัศรายุทธ ศรีใจอินทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To propose academic administration strategies based on an educational quality assurance system in small multigrade elementary schools. Data collection methods are the questionnaires, the interviews and the analysis of international research. The representative samples are 265 school administrators and academic teachers in small multigrade elementary schools.The strategies used are the analysis of the environment, tasks, conditions and problems of academic administration strategies based on an educational quality assurance system in small multigrade elementary schools. Moreover, the interview from the upscale schools and foreign researches are included in the strategies. The strategies have been reviewed twice by resource people until acquiring feasible academic administration strategies based on an educational quality assurance system in small multigrade elementary schools. The research found that external environment of small multigrade elementary schools is likely an enabling factor and is an opportunity especially in the aspects of cultural society, technology, laws and politics. It is also related to a community participation and a use of local academic resource technology supported by several education laws. However, the economy of all regions is the main obstacle to hinder the support of student education budget appropriately. The internal environment of most schools is strong. Nevertheless, the lack of specialists in each major is a weakness. Academic administration strategies based on an educational quality assurance system in small multigrade elementary schools consist of 7 parts which are 1) 1 strategy for school curriculum development 2) 7 strategies for learning process development 3) 2 strategies for academic media and technology development 4) 10 strategies for educational quality assurance system development 5) 2 strategies for private individual’s academic strength support 6) 2 strategies for measurement and credit transfer and 7) 8 strategies for other aspects which help support the academic administration strategies and learning process in multigrade elementary schools.